Button Hole Effect: A Rare Complication Following Irreducible Traumatic Posterior Hip Dislocation with Posterior Acetabular Fracture and Tissue Entrapment. - Munuo, Elibariki J.; Mandari, Faiton N. (International Journal of Health Sciences, 2026)
Purpose: Most hip dislocations are not well-reported in developing countries. Our current study aims to explain the trauma, its clinical presentation, goal-standard treatment, prognosis and the functional outcome. Methods: Convenience sampling was used to recruit participants, and demographic data were collected and recoded. Findings: Incarcerated posterior capsule, labrum and joint pushed out of the acetabulum cup and posterior acetabulum wall fracture, which contributed to poor reduction failure. It was therefore concluded that the management of a complex, persistent, irreducible hip joint dislocation and fracture involving a posterior acetabular fracture in a young patient was open reduction and acetabular reconstruction. Recommendations. Orthopaedic and trauma emergency surgeons need to immediately diagnose and point out the type of dislocation and whether it is isolated. In cases of irreducible posterior hip dislocations, an emergency surgical posterior approach must be adopted immediately to clean and repair all interposed tissue and any associated injuries to the capsule, labrum, capsules and muscles.